Vecuronium bromide: preferred suicidal drug among medical professionals – a case report - Krishna, Varun; Subramanyam, Sunil (Journal of Forensic Medicine and Toxicology, 2026)
We report a case of suicidal death due to self-administration of intravenous vecuronium bromide by a nursing student.  Toxicological analysis confirmed the presence of vecuronium bromide. Postmortem findings, toxicological analysis, and  crime scene investigation indicated a suicidal manner of death, with the cause attributed to respiratory paralysis resulting  from vecuronium injection. Skeletal muscle relaxants act either peripherally at the neuromuscular junction or centrally  on the cerebrospinal axis to reduce muscle tone. Neuromuscular blocking agents are commonly used in general anesthesia during surgery to induce muscle relaxation. Centrally acting muscle relaxants are primarily used for treating painful  muscle spasms and spastic neurological disorders.
Keywords: Vecuronium bromide; Muscle relaxant; Suicide; Nursing student